Upaya Penurunan Tekanan Darah Melalui Program Senam Hipertensi di Kota Palembang - Anjarwati, Dewi; Imardiani, Imardiani; Adisti, Adisti; Hawarsa. R, Afebteri; Adinda, Agnes; Agustina, Diah; Pratama, M. Gilang Yudha (Pusat Penelitian dan Pengabdian kepada Masyarakat, Politeknik Kesehatatan Kemenkes Palembang, 2025)
Hypertension is a health problem with an increasing prevalence worldwide, including in Indonesia. This condition is characterized by a systolic blood pressure of ≥140 mmHg and/or diastolic pressure of ≥90 mmHg. The high incidence of hypertension and its impact on patients require healthcare professionals to take part in prevention and health promotion efforts. Hypertension management can be carried out pharmacologically through medication and non-pharmacologically, one of which is hypertension exercise. This community service activity involved 27 residents of Banten 2, with blood pressure measurements taken before and after the hypertension exercise. The results showed that the average blood pressure before the exercise (pretest) was 140.56 mmHg (systolic) and 89.78 mmHg (diastolic), while after the exercise (posttest), the average decreased to 133.04 mmHg (systolic) and 86.15 mmHg (diastolic). These findings indicate a significant reduction in blood pressure after the implementation of hypertension exercise. Keywords: Hypertension, Community Service, Hypertension Exercise